2022
DOI: 10.1007/s11356-022-22717-2
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides monitoring in surface water of a subsistence agricultural catchment in Uganda using passive samplers

Abstract: Pesticides are intensely used in the agricultural sector worldwide including smallholder farming. Poor pesticide use practices in this agronomic setting are well documented and may impair the quality of water resources. However, empirical data on pesticide occurrence in water bodies of tropical smallholder agriculture is scarce. Many available data are focusing on apolar organochlorine compounds which are globally banned. We address this gap by studying the occurrence of a broad range of more modern pesticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…Indeed, it is commonly monitored in soils, ground water, and surface water, as well as in solid and liquid dietary samples. Thus, there is no doubt that the misuses of CPF and other organophosphate pesticides can have adverse effects on non-target organisms, including humans [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is commonly monitored in soils, ground water, and surface water, as well as in solid and liquid dietary samples. Thus, there is no doubt that the misuses of CPF and other organophosphate pesticides can have adverse effects on non-target organisms, including humans [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have been conducted in Uganda to investigate the presence and concentrations of emerging pollutants in different environmental systems in Uganda for example in water (27,28), sediments (27,29), surface waters (30)(31)(32), food crops (33,34), edible insects (35), breastmilk (36) and in fish (30). These studies have identified a range of compounds, including pharmaceutical residues (e.g., antibiotics, analgesics) (26,37,38), personal care products (e.g., fragrances, UV filters) (39), pesticides (e.g., herbicides, insecticides) (27,35,40,41), industrial chemicals (e.g., flame retardants, plasticizers) (36,39,42), microplastics and heavy metals (43)(44)(45). The concentrations of emerging pollutants reported in the literature vary depending on the sampling location, environmental matrix, and analytical techniques used.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies conducted in Uganda have investigated the sources, presence, and concentrations of CoCs in various environmental systems, including water bodies [31,32], sediments [31,33], surface waters [34][35][36], food crops [37,38], edible insects [39], breastmilk [40], and fish [34]. These studies have identified a range of compounds, including pharmaceutical residues like antibiotics and analgesics [30,41,42], personal care products like fragrances and UV filters [43], pesticides like herbicides and insecticides [31,39,44,45], industrial chemicals like flame retardants and plasticizers [40,43,46], microplastics, and heavy metals [32,47,48]. The reported concentrations of these CoCs exhibit variation depending on the sampling location, environmental matrix, and analytical techniques used.…”
Section: Introductionmentioning
confidence: 99%